A review on the prospective use of chicken manure leachate in high-rate anaerobic reactors. Issue 1 (February 2021) - Alba Reyes, Yasmani; Barrera, Ernesto L.; Cheng, Ke-ke
Graphical abstract: Highlights: Recent advances in chicken manure leaching were introduced. Strategies to improve anaerobic digestion using high-rate anaerobic reactors were reviewed. CFD is an appropriate tool for modeling leachate systems. The biorefinery concept through anaerobic digestion in the Cuban context was discussed. Abstract: The global production of chicken arises over the world, which leads to increasing manure generation and environmental problems. Anaerobic digestion (AD) is a well-known process to produce biogas from biomass. Chicken manure (CM) is considered as a feedstock for biogas production due to its high organic load, but there are some challenges to be considered, such as the heterogeneity and the high solid content. To overcome these issues, pretreatments techniques that enhance biogas production could be used. In this context, the use of the leachate process for CM pretreatment could be a novel alternative producing an easily biodegradable liquid substrate for AD. High-rate anaerobic reactors (HRAR), as mature technologies in the market, represent an opportunity for its technological simplicity and economy. Improvements of AD with leaching pretreatment were studied considering the use of HRAR as recent achievements to produce biogas and perspectives in the world. For mathematical modeling, the leaching process with CM as substrate, Computational Fluid Dynamics (CFD) methods are presented as a numerical simulation tool for a better understanding of the process. The integration of the leaching-efficient AD process in a biorefinery approach in a developing country using CM as a substrate could diversify its productions, in addition to reducing emissions to the environment. The results obtained became a tool for decision-makers and researchers about the implementation of leaching pretreatment prior to high-efficiency technologies for CM management in Poultry Farms to obtain the highest benefits, not only in Cuba but also in other developing countries with a similar situation. Production of biogas from CM is a technical solution that contributes to substitute fossil fuels by renewable energy.